“Só é bella de facto a mulher que tem saude”: beleza feminina nas páginas do Almanaque d’A Saúde da Mulher nas décadas de 1930 e 1940 - dos Santos Soares Junior, Azemar; Lima de Morais, Ana Karoline (Temporalidades, 2019)
This article aims to analyze female beauty in the 1930s and 1940s from the tonic advertisements "The health of women" published in the Women’s Health Almanac. The purpose of this annual periodical was to advertise the medicines of the Daudt & Oliveira laboratory. To conduct this study, we approach the reflections of Georges Vigarello (2006) and Denise Sant’Anna (2000) to reflect on the historicity of the concept of beauty and the cultural changes that modify it both in the West and in Brazil, especially since the second half of the 19th century and the first half of the 20th century. We will analyze the advertisements using the contributions of Maria do Rosário Gregolin (2011), thinking image and statement as a whole that composes a sense. We sought to show how the health of the female reproductive organs is presented in the periodical as the main source of not only health, but beauty and well-being.